막여과 공정에 의한 부영양화 호소수의 처리 - 김지연; 현길수 (한국수처리학회지, 26(4), 2018)
A lake water being used as drinking water source has been focused on the quality despite the limitation of the quantity. In particular, degradation of water quality can result from various pollutants sources including multiple land use activities. Algae blooms seriously threaten water quality and the supply of drinking water. In this study, the performances of membrane filtration (MF) using stirred dead end filtration cell(membrane module: material; PVDF, pore size; 0.22㎛) on pollutants removal with dissolved organic matter(DOC) and algae loading in an eutrophicated lake water was assessed. Batch tests were carried out with artificial water using eutrophicated lake water. Applied membrane permeate flux was 0.5 m3/m2.d. Influent concentrations were in the range of UV254 <0.24cm-1, DOC <9.5 mg/L, chlorophyll a (chl-a) 220㎍/L, dissolved TN(DTN) 0.6mg/L, and DTP 0.02mg/L. As a result, the chl-a concentration showed a maximum value on 20 day and the concentration of DOC have begun increasing from the initial stage of algae growth. For taste and odor removal, MF process achieved relatively low removal of approximate 12% for geosmin and 2-MIB. The permeate flux of MF also decreased with increase of TMP, which was 8 times greater than initial TMP. This result indicates the MF process coupled with a pretreatment processes such as activated carbon adsorption and/or coagulation and oxidation in order to mitigate membrane fouling as well as the production of good quality. KCI Citation Count: 0